COMPREHENSIVE DESCRIPTION OF THE HEALTHCARE SYSTEM IN UZBEKISTAN - Bekzodbek Komilov; Yodgorbek Ismoiljonov; Zafar Juraev (Journal Park Publishing, 2024)
Uzbekistan's healthcare system is a mix of public and private providers, with the government playing a significant role in the delivery and regulation of healthcare services. The Ministry of Health is the main governing body responsible for healthcare policy and planning in the country. Access to healthcare in Uzbekistan is universal, with the government providing healthcare services to all citizens and residents. In Uzbekistan, universal healthcare access is a key feature of the healthcare system. The government of Uzbekistan has implemented policies to ensure that all citizens and residents of the country have access to healthcare services, regardless of their income or social status. This means that healthcare services are available to everyone, including those who are employed, unemployed, self-employed, or retired.
Keywords: healthcare system, government-funded system, private providers, primary healthcare focus.